Violências contra mulheres e o discurso jurídico: Um estudo de sentenças criminais da 1ª Vara Criminal do município de Vila Velha/ES – 1975-2010 - Soares, Maria Angela Rosa (2021)
The thesis analyzes the legal discourse produced in in 191 (one hundred and ninetyone) criminal sentences in the municipality of Vila Velha, State of Espírito Santo, Brazil, from 1975 to 2010. The methodology adopted was the Critical Discourse Analysis (CDA), which allows for the identification of discourses and their permanencies, as well as the silences and the unspoken that reflect how the Law perceives women and who is the woman for the Law. The analyzed sentences strengthen the hypothesis that the discourse produced in the legal field has been presented more as a reproducing instance of historical inequalities than as a catalyst for solutions in this type of conflict. The belief in the neutrality of the legal field produces a language that reinforces gender inequalities and, consequently, does not resolve the violence resulting from the patriarchal culture that is still strongly present in the 21st century. The legal field is hierarchical, formal, elitist and does not act from the perspective of intersectionality when analyzing legal processes, despite the advances and contributions of various feminist researches. The technicality of this field does not consider the complexity of social relations and, in this way, reinforces the “biological destiny” of women and their consequent social inferiority, contributing to perpetuate inequalities and, particularly, violence. The result of the work shows that the gender inequality produced by patriarchal power relations produces the rate of violence against women currently in force in Brazilian society, in general, and in particular in the municipality that was the object of the study, as a long-standing social problem. duration. The research carried out indicates the perception of women as being inferior since the most remote times and the reproduction of this belief over the centuries, with new clothes, but with the same essence, that is, the desire to control the female existence by restricting her body, your desires, your abilities, your capabilities and all your potentials. The thesis emphasizes the legal discourse because it is understood as a central factor in dealing with violence involving women, as this violence directly affronts Human Rights, whose guarantee depends on the performance of the legal field. It was assumed that Brazilian legal education is “technicist”, which makes it difficult for professionals in this area to perceive the socio-historical construction of gender inequalities and the power relations that maintain them and, in this sense, the judicial system Brazil reproduces these inequalities, acting against the advances that feminist movements have achieved since the 19th century. Socially approved roles for each sex are further defined based on the sexual binarism that defines sex as a biological inheritance, in a deterministic perspective and without considering the social changes that redirect female roles. It is expected that the research will contribute to a reflection on a more humanistic legal education that is open to diversity, breaking with traditional paradigms and forming legal thinkers who work towards a less unequal society, that is, who effectively seek the justice.